Implementation of CWLS SW001 as a Productive Waqf from the Perspective of Maqashid Shariah - Hasibuan, Abdul Razak; Achiria, Siti (Unisia, 2024)
This study investigates the implementation of Cash Waqf Linked Sukuk (CWLS) SW001 as a tool for integrating Islamic social finance with modern investment practices. CWLS SW001 represents a transformative approach to mobilizing waqf funds, addressing socio-economic challenges, and adhering to Maqashid Shariah principles. The primary objective of the research is to evaluate the sukuk’s operational framework, its alignment with Islamic ethical principles, and its socio-economic contributions, particularly in the healthcare sector. Using a qualitative descriptive methodology, this study examines secondary data, including official reports and academic literature, to assess CWLS SW001’s mechanisms and impacts. The analysis is structured around Maqashid Shariah, focusing on objectives such as protecting life (hifdz an-nafs) and wealth (hifdz al-mal). The findings reveal that CWLS SW001 effectively channels waqf funds into productive and socially impactful projects, such as constructing a retina center and free cataract surgeries for underprivileged individuals. The sukuk’s operational model ensures transparency, financial sustainability, and compliance with Islamic principles. Despite its success, challenges remain, including limited public awareness and regulatory barriers hindering broader adoption and scalability. This study contributes to the growing body of knowledge on Islamic finance by demonstrating the potential of CWLS to address contemporary socio-economic issues. It highlights the need for strategic interventions, including enhanced literacy campaigns and regulatory reforms, to optimize the instrument’s impact and expand its applications across diverse sectors. The research underscores CWLS’s role as a replicable model for innovative and ethical financial practices.